Repetitive control for high-performance resonant pulsed power supply in radio frequency applications - Ji, Chao; Zanchetta, Pericle; Carastro, Fabio; Clare, Jon C. (IEEE, 2013)
This paper presents a novel three phase series resonant parallel loaded (SRPL) resonant converter topology for radio frequency (RF) applications. The proposed converter is capable to produce as output voltage a series of “long pulses”, each one lasting 1ms in time. Three individual single phase resonant stages are able to operate independently in conjunction with three separate single phase output rectification stages. Due to this important feature, the converter has a strong ability of rejecting the influence of unbalance in the resonant tanks. A PI + Repetitive Control (RC) strategy has been used for the output pulsed voltage regulation, resulting in a fast rise time, reduced overshoot, and constant amplitude. The soft-switching of semiconductor devices is ensured at full power by a combined frequency and phase shift modulation (CFPS), even in the presence of large tank unbalances.